Lesser omentum of white rats: structural and functional characteristics - Maksymenko, O.S.; Stupak, D.S.; Hryn, V.H. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. According to the literature, all mammals have two omenta, one of which is the greater omentum and the other one is the lesser omentum, but white rats have two additional derivatives of the visceral peritoneum, homologous in structure to the greater omentum - called the epididymal omentum. Today, the greater omentum is comprehensively studied and arouses great interest among researchers, in turn, the lesser omentum is not popular among scientists, as a result of which many details of its anatomical and histological structure remain undisclosed. Objective. To study the morpho-functional features of the structure of the lesser omentum of white rats through a bibliographic analysis of the literature. Methods. This bibliographic analysis is based on published articles, books, textbooks, and monographs. The search for which was carried out on the worldwide network "Internet" in the scientific and metric databases of Google Scholar, Web of Science and PubMed, foreign sources of literature and the National Library of Medicine. Results. The lesser omentum is formed due to the successive transition of the duplication of the peritoneum, from the lower surface of the liver to the lesser curvature of the stomach and duodenum. At the small curvature of the stomach, the leaves that form the lesser omentum diverge and cover the front-upper and back-lower walls of the stomach. The lesser omentum consists of the hepatogastric ligament, which is an extremely thin and transparent membrane, and a thicker, transparent membrane - the hepatoduodenal ligament, which is attached to the duodenum. Microscopically, it consists of two main structural elements: thin fenestrated translucent membranes and adipose tissue-rich areas containing milky spots that may play a role in the immune defense of the peritoneal cavity. Conclusion. So, according to the analysis, the lesser omentum mainly performs a connecting role and provides support and stabilization of the organs of the abdominal cavity between which it is located.